Sustainable waste management and organizational performance of food and beverage firms - Michael Ikenna Udodiugwu (Annals of Management and Organization Research, 2024)
Purpose: Evidence shows that Numerous sustainability measures have been put in place to mitigate the huge impact of uncontrollable solid waste disposal. This study was conducted to investigate the impact of waste management on the performance of food and beverage firms. Research Methodology: The study surveyed nine (9) food and beverage firms, and data were collected with the use of questionnaire from a sample population of one hundred and fifty-one (151) respondents, through a simple random technique. The multiple regression analysis contained in the Statistical Package for Social Sciences (SPSS) IBM version 23 was used to analyze the data obtained from the field of study. Results: The findings from this study revealed a positive significant impact of recycling on resource conservation, while the second finding showed a negative impact of waste incineration on employee health and safety. Limitations: Waste includes solid, liquid, and gas components. However, prior studies have focused on other forms of waste and industrial goods manufacturing firms, specifically solid waste, as the interest area covered only food and beverage manufacturing firms. Contribution: This study addresses one of the major issues related to global warming that occurs as a result of waste dumping and excessive burning. This study has helped curb these challenges by recycling waste and conserving untapped resources for sustainable performance and the healthy coexistence of humans